2018
DOI: 10.3389/fmicb.2018.02023
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Microbial Eukaryotes From Surface to the Hadal Zone of the Mariana Trench

Abstract: Marine microbial eukaryotes are ubiquitous, comprised of phylogenetically diverse groups and play key roles in microbial food webs and global biogeochemical cycling. However, their vertical distribution in the deep sea has received little attention. In this study, we investigated the composition and diversity of the eukaryotes of both 0.2–3 μm and >3 μm size fractions from the surface to the hadal zone (8727 m) of the Mariana Trench using Illumina MiSeq sequencing for the 18S rDNA. The microbial eukaryotic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 91 publications
5
39
0
Order By: Relevance
“…A global survey indicated that the distribution of protists in the upper ocean is predominantly structured by oceanographic basin, pointing to dispersal limitation [4,5], while in the bathypelagic layer, protist assemblages appear to be structured by water masses [6]. Previous studies on the distribution of protists along the water column are limited to a few specific oceanic regions and indicate a clear differentiation between epipelagic and deep ocean communities [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A global survey indicated that the distribution of protists in the upper ocean is predominantly structured by oceanographic basin, pointing to dispersal limitation [4,5], while in the bathypelagic layer, protist assemblages appear to be structured by water masses [6]. Previous studies on the distribution of protists along the water column are limited to a few specific oceanic regions and indicate a clear differentiation between epipelagic and deep ocean communities [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…19 Due to the special ecological environments around the trench, it may contain abundant fungal resources. In the last decades, there were several studies on the diversity of microbes including actinomycetes, 20 bacteria, fungi and Picoeukaryotic isolated from sediments and seawaters in the Pacic Ocean and Mariana Trench 8,11,14,[20][21][22] by culture and molecular approches.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are active members of deep-sea sediment communities (Pachiadaki et al, 2016; Morales et al, 2019), but in this ecosystem, they are far more poorly characterized than bacteria and archaea (Edgcomb et al, 2011; Nagano and Nagahama, 2012; Dekas et al, 2016; Xu et al, 2018). In deep waters, fungi are well adapted to the total absence of light, low temperatures, and high hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in studying fungal communities in deep-sea environments using culture-dependent and, to an increasing extent, culture-independent methods. Abundant fungal populations have been observed in a variety of deep-sea locations such as asphalt seeps in Sao Paulo Plateau (Nagano et al, 2017), methane seeps in the Kuroshima Knoll (Takishita et al, 2006), hydrothermal vents in the Mid-Atlantic Ridge (Le Calvez et al, 2009; Xu et al, 2017), sediments of the Peru Trench (Edgcomb et al, 2011), the East Indian Ocean (Zhang et al, 2014), the High Arctic (Zhang et al, 2015), the Mariana Trench (Xu et al, 2016, 2018), the Yellow Sea (Li et al, 2016), the Mediterranean Sea (Barone et al, 2018), the Yap Trench (Li et al, 2019), and subsurface sediments in Suruga-Bay (Nagano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%